Strength and Durability Characteristics of Cement-lime Mortars with Fly Ash and Slag as Aggregate Substitutes - Kończalski, Paweł; Katzer, Jacek (Periodica Polytechnica Civil Engineering, 2021)
The global consumption of sand by the concrete industry has increased significantly over the years. Natural sand has become a desired commodity in numerous regions of the world. To protect both the existing resources of natural sand and utilize waste materials, drastic actions are urgently needed. The production of cement mortars, which are solely based on fine aggregate, is responsible for the large consumption of natural sand. In the described research program, we proposed to substitute 50 % of the natural sand in mortars with fly ash and slag. The strength properties and durability characteristics of the new mortars were tested. It was proved that mortars with fly ash and slag can be used for specific applications in civil engineering. Areas for future research associated with the mortars in question were also pointed out.